Reframing Street Child Governance in Indonesia: A Mixed-Methods Analysis through Parsons᾿ Systems Theory and Islamic Hisbah Framework - Yulia Tri Samiha; Middya Boty; Annisa Fauzia Apriliani; Althaafi Abdillah; Eby Sania Awalia; Iga Mawarni (Faculty of Sharia, Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
The street children phenomenon is a continuing and complex social issue in South Sumatra, Indonesia, which is influenced by family dysfunctions and structural poverty. Using the concept of Islamic hisbah law and applying the organic systems approach based on Talcott Parsons and the utilitarian view, this study discusses social service interventions for the problem of street children in South Sumatra in terms of their strategy, implementation, difficulties, and success. Employing a mixed-methods approach with a sequential exploratory design, the study investigates the street children management implemented by the Social Services in Palembang city, Banyuasin district, and Ogan Ilir district via interview, observation, and survey. The findings show a well-defined intervention strategy with three main stages: outreach, guidance and training, and repatriation, with persuasive and rehabilitative approaches predominating over the punitive measures. Nevertheless, implementing the model is hindered by three key challenges: limited transportation facilities, budgetary limitations, and inadequate number of field staff members. Based on six performance indicators, it is seen that inter-agency collaboration had the highest score of 85, followed by responsiveness to children’s need (83), program planning (82), effectiveness of implementation (81), adequate resources (80), and finally monitoring, evaluation, and accountability (77). Overall, the intervention model’s implementation received an average score of 81 (in good category), suggesting a fairly effective approach. One unique feature of this study is the application of Islamic hisbah concept to modern social service system through emphasis on the significance of collective responsibility for society as a whole, enhanced involvement of communities, and better monitoring mechanisms.